DETERMINATION OF SOME KINDS OF IMPORTANT INGREDIENTS OF COMPONANTS AND BIOLOGICAL ACTIVITY OF GARCINIA COWA FRUIT - Thi Thu Hang, Nguyen (Journal of Forestry Science and Technology, 2018)
Tai Chua (Garcinia cowa Roxb.) in the plant family of Clusiaceae was a wealthy medical resource. For the industrial use in fruit processing, we need to understand the components extracted in Tai Chua and their bio-activity as well. We found that Tai Chua fruits had 90.28 - 93.43% humidity, 3.05 - 4.36% total acids, 3.03 - 4.34% total orgnanic acids, 0.7 - 0.74% total carbonhydrates, and 57.75 - 64.75 mg/100 g vitamin C. The extract in ethanol showed the high anti-bactrial effects. Three fruit stages were tested, including the young, ripen and over-ripen. The ripen fruits had high nutrients, vitamin C, and strong antibactrial activities. So it had a poten for the production of the foods originated from Tai Chua. The foods would be able to improve detoxicity, anti-imfamatory, antioxidants, slow aging and immunity.